Treatment of patients with multiple myeloma complicated by renal failure with bortezomib-based regimens - Roussou, M.; Kastritis, E.; Migkou, M.; Psimenou, E.; Grapsa, I.Irini; Matsouka, C.; Barmparousi, D.; Terpos, E.; Dimopoulos, M.A. (Leukemia and Lymphoma, 2008)
Renal failure is a common feature of multiple myeloma and a major management problem. However there is limited data regarding the reversibility of renal failure, the kinetics of serum creatinine and the safety of novel agents such as bortezomib when administered to newly diagnosed or relapsed/refractory patients with renal failure. Patients and Methods. We evaluated 20 consecutive patients with newly diagnosed or relapsed/refractory multiple myeloma and renal failure, defined as a serum creatinine ≥ 2 mg/dl. All patients received bortezomib with dexamethasone or in combination with other agents (thalidomide, doxorubicin or melphalan). Results. Reversal of renal failure was documented in 40% of all patients and the median time to reversal was 17 days. Moreover 10 patients (50%) had 50% decrease in serum creatinine and the median time to decrease was 35 days. Some decrease of creatinine was documented in 85% of patients. The objective response rate was 65%. Toxicities were similar to those seen in myeloma patients without renal failure. Conclusions. Bortezomib based regimens can be administered to myeloma patients with renal impairment and their toxicity and efficacy are similar to those observed in patients without renal impairment. Moreover, bortezomib-based regimens induce improvement of serum creatinine in most patients and reversal of renal failure in approximately one-third.
Keywords: bortezomib; myeloma; Renal failure